Plant hormones in defense response of Brassica napus to Sclerotinia sclerotiorum - reassessing the role of salicylic acid in the interaction with a necrotroph - Nováková, Miroslava; Sašek, Vladimír; Dobrev, Petre I; Valentová, Olga; Burketová, Lenka (Plant physiology and biochemistry, 2014)
According to general model, jasmonic acid (JA) and ethylene (ET) signaling pathways are induced in Arabidopsis after an attack of necrotroph, Sclerotinia sclerotiorum (Lib.) de Bary. However, abscisic acid (ABA) and salicylic acid (SA) also seem to play a role. While signaling events in Arabidopsis have been intensively studied recently, information for the natural host Brassica napus is limited. In this study, multiple plant hormone quantification and expression analysis of marker genes of the signaling pathways was used to gain a complete view of the interaction of B. napus with S. sclerotiorum. Strong response of ET biosynthetic gene ACS2 was observed, accompanied by increases of SA and JA levels that correspond to the elevated expression of marker genes PR1 and LOX3. Interestingly, the level of ABA and the expression of its marker gene RD26 were also elevated. Furthermore, induction of the SA-dependent defense decreased disease symptoms. In addition, SA signaling is suggested as a possible target for manipulation by S. sclerotiorum. A gene for putative chorismate mutase SS1G_14320 was identified that is highly expressed during infection but not in vitro. Our results bring the evidence of SA involvement in the interaction of plant with the necrotroph that conflict with the current model.
Keywords: Salicylic Acid; Necrotroph; Effector; Ascomycota; Chorismate mutase; kyselina salicylová; Salicylic acid; Sclerotinia sclerotiorum; Defense signaling pathways; regulace genové exprese u rostlin; Brassica napus; Gene Expression Regulation, Plant